Optimization of Machining Process on Coated Tungsten Carbide Electrode Tool and Titanium Alloy Workpiece Using EDM: A Critical Review - Singh, Newton Kumar; Rao, P. Sudhakar; Saidaiah, Kalakonda (Applied mechanics and materials, 2024)
Commercial applications for Ti 6Al 4V, an alloy composed of titanium, aluminium, and vanadium, are possible. The features of titanium alloy include: Lightweight, non-magnetic, high melting point, outstanding fatigue strength, superior specific strength, great corrosion resistance, and biocompatibility. Reviewing the electro-discharge machining of titanium alloy (Ti 6Al 4V) as a workpiece, silicon carbide particle combined with EDM oil, and coated tungsten carbide electrode, this research examines this process. Dielectric fluid's impact on microhardness, surface finishing, TWR, and MRR. MRR is raised by silicon particles and coated tungsten carbide electrodes with EDM fluid. According to the study, the most important input parameters for determining TWR, MRR, surface finishing, and micro-hardness are voltage, current, pulse on time (Tonne), and pulse off time (Toff).